INVERSI IMPEDANSI ELASTIK UNTUK MENGESTIMASI KANDUNGAN RESERVOIR BATUPASIR LAPANGAN â€œVeâ€ FORMASI CIBULAKAN CEKUNGAN JAWA BARAT UTARA - Aisyah, Veratania; Harmoko, Udi; Mualimin, Mualimin (BERKALA FISIKA, 2011)
An Elastic Impedance inversion was carried out Â to determine sandstone reservoir characterizationÂ of â€œVeâ€ Field Cibulakan Formation, Northwest Java Basin. There are many steps of data processing toÂ analize a well log data in order to get sensitive angle of lithologic characterization. Mudrock Line equationÂ was applied to obtain Vs log data of the research target zone. The next step, we did Well seismic tie toobtain horizon that approach the real geological zone. Initial model was made by used a control well andDST 5 horizon. Sparse Spike inversion gives the most accurate result than two other one. According to thevolume inversion, we plotted to a map show the contrast of sandstone lithology. Based on Elastic Impedanceinversion analysis, we estimate the rangeof sandstone reservoir impedance:1348 (m/s)gr/cc â€“ 1365(m/s)2gr/cc. Crossplot analysis result between log Elastic Impedance and log Gamma Ray shows that 35isthe best angle of the sandstone and shale lithologic sparation.Keyword: Elastic Impedance, AVO, inversion, Mudrock Lin